EFEKTIVITAS METODE STAD BERBANTUAN LKS TERHADAP HASIL BELAJAR PAK KELAS 3 SD - Krisdayanti Elisabeth Br. M; Hartutik Hartutik; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2022)
The problem in this study is that the low learning outcomes of students are caused by students having difficulty relating and understanding the meaning of the scriptures in examples of daily life, the lack of attention of students when the teacher gives explanations related to learning materials, the learning method used by the teacher is the lecture method so that learning be focused on the teacher only (teacher-centered). This study aims to: 1) to determine the effect of student collaboration using the STAD method assisted by LKS on student learning outcomes, 2) to determine the difference in learning outcomes after and before using the STAD method assisted by LKS, 3) to determine the effectiveness of the STAD method assisted by LKS on student learning outcomes. This type of research is pre-experimental with a one-group pretest-posttest design. This study used only one group, namely the experimental group and the sample used was 10 people, namely, grade 3 SD Kebon Dalem Semarang. This group used 2 measurements, namely the pretest was carried out to determine the students' initial understanding before the LKS-assisted STAD method was applied, then the posttest was carried out after the LKS-assisted STAD method was applied. Based on the results of hypothesis testing, it was found that: 1) there was an effect of student collaboration using the STAD method assisted by LKS by 82%, 2) there was a significant difference in the application of the STAD method assisted by LKS on learning outcomes, seen from the acquisition of a sig (2- tailed) score of 0.000 means accepting H1 and rejecting H0, 3) ​​an increase in learning outcomes with an interpretation of the effectiveness of N-Gain by 74% is included in the category of quite effective in using the STAD method assisted by LKS.